Pengembangan kerangka manajemen risiko pada perbankan syariah - Rafi, M. Zahid Zakh (Maliki Interdisciplinary Journal, 2024)
Islamic banking, like other business institutions, is exposed to various risks inherent in its primary operations. In business, risk is understood as the potential for adverse outcomes and can arise at any stage of decision-making. Islamic banking encounters distinct risks compared to conventional banking due to its unique characteristics. Therefore, establishing a robust risk management framework in Islamic banking is crucial, particularly focusing on risk identification, assessment, mitigation, and monitoring. This paper aims to explore the theoretical aspects and practical implementation of risk management in Islamic banking. The study will encompass the identification of risks specific to Islamic banking, the stages of risk management, risk management models, and the development of a comprehensive risk management framework tailored to Islamic banking.